Expectations, Experiences and Perceptions of Oral and Maxillofacial Surgery Residents to Training in Nigeria. (24th May 2021) - Fomete, Benjamin; Adebayo, Ezekiel T.; Oginni, Fadekemi O.
Abstract: Purpose: How surgical residents fare during their training could enhance job satisfaction and fulfilment post‐training. But there is paucity of literature on the experiences of oral and maxillofacial surgery (OMS) trainees during residency training. The aim of this study was to report the expectations, experiences and perceptions of OMS residents towards training in Nigeria. Methods: Cross‐sectional study of OMS residents in accredited Nigerian training institutions was conducted between September and December, 2017. Study tool was adapted from that used for general surgery residents in the United States. Results were analysed using Microsoft Excel for Windows 10. Results: Sixty‐eight of seventy‐three questionnaires were returned (response rate was 93%). More respondents were males (86.8%) than females (13.2%). 44.1% of all respondents were aged 35–39 years. Senior residents (n=31, 45.6%) were more than those in the junior cadre. The most important reason for choosing OMS residency training was for knowledge (72.1%) followed by the prospect of better pay (8.8%). Most residents believed their opinions were important (66.7%) and looked forward to their daily work (72.1%) but were dissatisfied with the didactic teaching aspect by consultants (57.3%) and felt the hours and stress of working were straining their family life, respectively (91.0% and 76.7%). Conclusion: Most OMS residents were happy and expected to gain knowledge from the training. However, some were dissatisfied with the training duration and level of didactic teaching by consultants and the impact of residency training on family life. There is need to improve didactic teaching and ensure adequate work/family balance for better OMS residency training in Nigeria.